Perlindungan Hukum terhadap Anak sebagai Penyalahguna Narkotika di Wilayah Hukum Polres Pelabuhan Belawan - Saragih, Denny Hardi Pranata; Zulyadi, Rizkan; Siregar, Taufik (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study was to analyze the legal protection arrangements for child narcotics abusers and their obstacles in the Belawan Harbor Police Legal Area. The research method used is descriptive method, while the data analysis technique uses qualitative. The results of the study indicate that the legal protection carried out against children as narcotics abusers in Indonesia based on Law No. 11 of 2012 concerning the Juvenile Criminal Justice System has been regulated starting from the process of investigation, arrest, detention, prosecution, examination in court and correctional. The Belawan Harbor Police Resort has made efforts to protect children who use narcotics by fulfilling children's rights during the investigation process, as well as seeking to resolve cases through diversion. Various obstacle factors faced by the protection of children who abuse narcotics are deviant behavior from child suspects, pressure on children from narcotics networks, the detention time of children is relatively short, there are restrictions on diversion requirements as non-repetition of criminal acts, and the cost of resolving cases through diversion is relatively large for costs. rehabilitation and consultation costs. It is recommended that the police not use children to uncover narcotics networks. The government needs to consider revising the SPPA Law by removing the diversion restriction as regulated in article 7 paragraph (2). The government needs to consider fully covering the costs of rehabilitating children who use narcotics at a more reasonable cost standard.